Adoptive immunotherapy with natural killer cells from peripheral blood CD34+ stem cells to prevent hepatocellular carcinoma recurrence after curative hepatectomy: a study protocol for an open-label, single-arm phase I study. Issue 11 (21st November 2022) - Ohira, Masahiro; Kobayashi, Tsuyoshi; Tanaka, Yuka; Imaoka, Yuki; Sato, Koki; Imaoka, Koki; Nakano, Ryosuke; Doskali, Marlen; Piao, Jinlian; Nakamura, Mayuna; Yoshida, Tetsumi; Ichinohe, Tatsuo; et al.
Abstract : Introduction: Hepatocellular carcinoma (HCC) remains a major clinical problem as more than half of these cases recur after radical resection. Natural killer (NK) cells are at the forefront of the innate immune system and attack microcarcinomas and circulating tumour cells. The objective of this study was to evaluate the feasibility and toxicity of peripheral blood CD34 + stem cell-derived NK cell infusion after radical hepatectomy for HCC. Methods and analysis: This is an open-label, single-arm, single-centre phase I study. Patients who have undergone initial hepatectomy for HCC with three or more risk factors for recurrence (≥10 ng/mL of Alpha fetoprotein (AFP), ≥360 mAU/mL of PIVKA-II, multiple tumours and ≥3 peripheral blood circulating tumour cells) will be enrolled and be treated with three peripheral blood CD34 + stem cell-derived NK cell infusions every 3 months. The primary endpoint will be safety assessment including the type and severity of adverse events, frequency of occurrence and duration of occurrence. The secondary endpoints will include survival, effect of immune response and clinical laboratory test results. Ethics and dissemination: Ethical approval of the trial was obtained from the Certified Committee for Regenerative Medicine Hiroshima University in Japan. The trial results will be shared with the scientific community at international conferences and by publication in a peer-reviewed journal. Trial registration number: jRCTb060200020.